A formação continuada de professores de matemática que atuam no ensino médio integrado à educação profissional (EMIEP) em Barra do Garças - MT - Silva, Lucenildo Elias da (2018)
It is now possible to perceive the great concern about the quality of education in the last stage of basic education. This concern occurs in Brazil, particularly from the last decades of the last century, with the presentation of proposals directed to the need for changes in the system of organization and supply of secondary education. These concerns arise from the severe transformations that occurred in the country from the 1980s, 1990s and the beginning of the XXI century, when several reforms of the educational system came to meet the demands of the structural adjustment of the neoliberal project begun at the time, with the orientation of international organizations, led by the World Bank. In this sense, the proposal indicates to another form of organization and intentionality of education for secondary education, and consequently for the teacher who acts in this stage of basic education. The research is entitled "The Continuing Education of Mathematics Teachers that work in Integrated Higher Education to Professional Education (EMIEP) in Barra do Garças-MT", linked to the PostGraduate Program in Education of the Federal University of Mato Grosso, Campus Cuiabá, in the Research Line Education in Sciences and Mathematics Education, and aims to analyze if the continuous training offered by the Center for Training and Updating of Basic Education Professionals (CEFAPRO) and the secretary of education of Mato Grosso state (SEDUC/ SUFP) to math teachers who work at EMIEP in the city of Barra do Garças-MT contributes to their professional development in the classroom in the perspective of the curriculum integrated with professional education. The research was developed under a qualitative approach and was developed in the municipality of Barra do Garças, state of Mato Grosso, in a CEFAPRO and a state school offering EMIEP. The subjects involved in the research were five mathematics teachers who work at EMIEP and two mathematics teachers who work at CEFAPRO. For the production of the data, we used semi-structured questionnaires, interviews and documentary analysis. In order to understand the concepts of integrated secondary education to professional education, we discuss the constitution of secondary education and the conceptions of integrated curriculum, the relation theory and practice in EMIEP, the integral and omnilateral formation of the young integrated high school subject, considering work as the educational principle and the quality of education of education supported by theoretical references that discuss the theme. Regarding the continuous formation of teachers, the discussions are based on the conceptions of teacher training, in the continuous aspect, as a possibility to improve the conditions of the teacher's performance in the EMIEP modality, under the protection of theorists who discuss the said theme. The data produced by this research reveal that the continuous training offered to EMIEP mathematics teachers in the state of Mato Grosso occurs in a non-specific way, presenting several gaps in its execution, which significantly weakens it, besides presenting multiple challenges that need be surpassed by CEFAPRO.